Interpreting Authentic Leadership: A Cross Cultural Comparison of A New Zealand University and Ghanaian University - Owusu-Bempah, Justice (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
National culture theory proponents have argued that due to differences in national cultures, expectations and preferences differ and this affect prioritizations in value systems. However, the authentic leadership (AL) theory presents an authentic leader as honest, transparent and behaves with integrity regardless of culture. By presenting AL this way, the proponents of the AL theory are discounting the effects of contexts/culture in the subjective interpretations and prioritizations of individuals in explaining constructs and concepts. This study, therefore, explored and compared the preferred authentic leadership attributes from leaders' and followers' perspectives using respondents from a Ghanaian university and a New Zealand university. The Q method was used to gather information from 60 respondents, 30 in each university. The findings show that the subjects, though in different cultural contexts, have some common shared preferences for certain authentic leadership attributes. However, there were some attributes that were country specific. This suggests that though certain authentic leadership attributes are universal whereas some are context specific and therefore in defining authenticity in leadership context specific preferences cannot be overlooked. The findings of study apart from being useful in the design of training programs to training practicing and upcoming leaders in universities, has also contributed a cross cultural dimension of authentic leadership attributes to the authentic leadership theory.